Flame retardant for super soft PVC products and method for preparing super soft PVC artificial leather

By using composite flame retardant in ultra-soft PVC materials, combining antimony trioxide and composite phosphorus nitrogen flame retardant, the problem of high-efficiency flame retardant in ultra-soft PVC materials is solved, and the flame retardant effect and smoke suppression performance are achieved better than the use of antimony trioxide alone.

CN119308147BActive Publication Date: 2025-04-22TAICANG WEILONG CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411856786.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-22
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient flame retardant in ultra-soft PVC materials, especially in the case of high plasticizer content, and alternatives to antimony trioxide are difficult to achieve a flame retardant effect comparable to those used alone.

Method used

A composite flame retardant is used, which contains antimony trioxide component and a composite phosphorus-nitrogen flame retardant component, including organic phosphinates, inorganic hypophosphites, phosphates, nitrogen-containing flame retardants, charcoal-forming agents and optional carbon layer synergists. Through multiple flame retardant mechanisms and formulation optimization, it matches the use of antimony trioxide.

Benefits of technology

High-efficiency flame retardant in ultra-soft PVC products with high proportion of plasticizers is achieved, reducing the amount of antimony trioxide, and the flame retardant effect is equivalent to or even exceeding the solution of using antimony trioxide alone, while reducing flue gas release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308147B_ABST
    Figure CN119308147B_ABST
Patent Text Reader

Abstract

The invention provides a flame retardant for an ultra-soft PVC product and a method for preparing the artificial leather, in particular, for an ultra-soft PVC leather material with a plasticizer content of 70-120 parts, and realizes efficient flame retardancy of the ultra-soft PVC through multiple flame retardant mechanisms and formula optimization, changes the current situation that antimony trioxide is the only option in the existing ultra-soft PVC flame retardant system, and realizes lower smoke release than using antimony trioxide alone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic hypophosphite flame retardants, and specifically relates to a flame retardant for super-soft PVC products and a method for preparing super-soft PVC artificial leather. Background Art

[0002] As one of the five general-purpose plastics, polyvinyl chloride (PVC) is widely used due to its excellent comprehensive performance. PVC itself is a flame retardant material with a chlorine content of up to 56% and an oxygen index of more than 45%. However, the light and heat stability of PVC is biased, and stabilizers need to be added to improve its light and heat stability. In addition, a certain amount of plasticizer is required to improve processing performance. According to the amount of plasticizer added, PVC can be divided into hard PVC, semi-hard PVC and soft PVC. The higher the plasticizer content, the softer the texture of the prepared composite material, and the easier it is to burn, and the more difficult it is to flame retard.

[0003] Due to the good physical properties and low cost of PVC, it is widely used in the plastic, cable and leather industries, among which the most widely used are the communication cable industry and the leather industry. The above applications all require the introduction of more plasticizers, especially the leather industry, which has high requirements for hand feel and needs to prepare ultra-soft PVC, which further increases the difficulty of flame retardancy. In the flame retardant application of soft PVC, antimony trioxide flame retardant is the best choice. Only 8-10 parts can be added to achieve high-efficiency flame retardancy of soft PVC. However, in recent years, with the restrictions on the use of heavy metals and the difficulty of mining mineral resources, antimony raw materials have been in short supply. The price of antimony trioxide has continued to rise, from 50,000 yuan / ton to 140,000 yuan / ton. Based on the comprehensive consideration of cost and environmental protection, substitutes for antimony trioxide have always been the focus of people's attention and development. The existing technology mainly starts with inorganic zinc borate, zinc stannate, ammonium molybdate, molybdenum oxide, etc. In addition, filler-grade magnesium hydroxide, aluminum hydroxide, talc, etc. are often used, but it is difficult to achieve the same flame retardant effect as antimony trioxide alone.

[0004] CN105086197 B discloses a solution for flame-retardant soft PVC compounded with antimony oxide, wherein the plasticizer content is 55-65 parts, and the total amount of flame retardant added is about 20 parts. Antimony trioxide is subjected to organic coating modification treatment, and is compounded with PVC soft glue prepared by ammonium molybdate and montmorillonite, achieving vertical combustion V-0 and an oxygen index of more than 30%, achieving a relatively ideal flame retardant effect.

[0005] CN108948596 B discloses a method for preparing a composite flame-retardant soft PVC resin, which introduces montmorillonite superacid and a small amount of antimony trioxide to prepare a PVC soft rubber material with better flame retardancy and better comprehensive mechanical properties. The invention involves 35-45 parts of plasticizer, which does not belong to the category of super-soft PVC products. In addition, the preparation and post-treatment of montmorillonite superacid are relatively cumbersome, which is not conducive to large-scale production and application.

[0006] CN 113214537 A discloses a composite flame retardant for polyvinyl chloride, which is compounded with antimony trioxide, zinc borate and ammonium polyphosphate. The inorganic particles are coated with ammonium polyphosphate to improve the compatibility with PVC. This patent combines pure inorganic powder with phosphorus-nitrogen flame retardant, and achieves more efficient flame retardancy in a formula of 30 parts of plasticizer. The total addition amount of flame retardant is about 10 parts.

[0007] CN 117265883 A discloses a composite flame retardant for artificial leather, wherein the composite flame retardant for PVC leather contains phosphate compounds, phosphate ester compounds, mineral soil compounds, borate compounds and transition metal oxides, and the weight ratio of PVC resin to composite flame retardant in the formula is 100: (6-8), and the addition ratio is relatively low, which can achieve higher oxygen index data and lower level combustion rate. However, the plasticizer content is not high, only about 50 parts, so the flame retardant difficulty is significantly reduced, and the composite flame retardant system contains phosphate ester components, especially tricresyl phosphate components, which are subject to various laws and regulations and are not suitable for environmental protection flame retardant requirements.

[0008] CN 109467845B discloses a flame retardant and smoke suppression PVC composite material and a preparation method thereof, wherein 95-110 parts of PVC resin and 35-45 parts of plasticizer are used. Phenylphosphonate and antimony trioxide are compounded as flame retardants to prepare the flame retardant and smoke suppression composite material. Antimony trioxide powder and organic salt are also combined to improve the compatibility with PVC, thereby achieving a better flame retardant effect than using antimony trioxide alone.

[0009] There are many similar inventions and studies, but these materials have not been tried and flame-retardant studies have been conducted in super-soft PVC. For most flame-retardant soft PVC materials, the plasticizer content is concentrated between 30 and 60 parts, and there are no reports on flame-retardant performance studies with more than 70 parts of plasticizer. Summary of the invention

[0010] In order to solve the above problems, the present invention provides a flame retardant for ultra-soft PVC products and a method for preparing ultra-soft PVC artificial leather, especially for ultra-soft PVC leather materials with a plasticizer content of 70-120 parts, and through multiple flame retardant mechanisms and formula optimization, high-efficiency flame retardant ultra-soft PVC is achieved, changing the current situation that antimony trioxide is the only choice in the existing ultra-soft PVC flame retardant system, and achieving lower smoke release than using antimony trioxide alone.

[0011] Specifically, on one hand, the present invention provides a compound flame retardant for ultra-soft PVC products, wherein the compound flame retardant comprises an antimony trioxide component and a composite phosphorus-nitrogen flame retardant component, wherein the composite phosphorus-nitrogen flame retardant component comprises: an organic phosphite, an inorganic phosphite, a phosphate, a nitrogen-containing flame retardant, a carbon former, and an optional carbon layer enhancer.

[0012] Furthermore, in the ultra-soft PVC product, the content of the plasticizer is 70-120 parts, preferably 80-110 parts, based on 100 parts by weight of the PVC resin;

[0013] Furthermore, the PVC product is artificial leather;

[0014] Furthermore, the mass ratio of the antimony trioxide to the composite phosphorus-nitrogen flame retardant component is 1:(1-2.33).

[0015] Furthermore, the specific mass composition percentage of the composite flame retardant is:

[0016] Antimony trioxide: 30%-50%;

[0017] Organic phosphinate: 5%-15%;

[0018] Inorganic hypophosphite: 5%-15%;

[0019] Phosphate: 10%-20%;

[0020] Nitrogen-containing flame retardant: 10%-20%;

[0021] Carbon-forming agent: 5%-10%;

[0022] Carbon layer enhancer: 0-5%.

[0023] Furthermore, the organic phosphite or inorganic phosphite is selected from: one or more of diethyl aluminum phosphite, diethyl zinc phosphite, diethyl calcium phosphite, diethyl-monoethyl composite aluminum phosphite, diisobutyl aluminum phosphite / dimethyl aluminum phosphite, aluminum phosphite, calcium phosphite, and lanthanum phosphite.

[0024] The phosphate is selected from: one or more of aluminum tripolyphosphate, zinc phosphate, magnesium phosphate, ammonium polyphosphate, melamine phosphate salt, and melamine polyphosphate salt; in the technical solution of the present invention, the phosphate can be used as a substance providing an acid source.

[0025] The nitrogen-containing flame retardant is selected from: one or more of melamine, dimelamine, melamine cyanurate, and guanidine carbonate; in the technical solution of the present invention, the nitrogen-containing flame retardant can be used as a substance providing a gas source and gas phase flame retardancy.

[0026] The carbon-forming agent is selected from one or more of: piperazine pyrophosphate, diethyl phosphinate piperazine salt, dicarboxyethyl phenyl phosphinate melamine salt, and triazine ring carbon-forming agent CFA.

[0027] The carbon layer synergist is selected from one or more of magnesium hydroxide, aluminum hydroxide, zinc stannate, hydroxy zinc stannate, zinc aluminate, aluminum silicate, zinc silicate, silicon dioxide, and zinc borate.

[0028] Another aspect of the present invention provides a method for preparing an ultra-soft flame-retardant PVC artificial leather, wherein the PVC artificial leather comprises three layers: a PVC surface layer, a PVC foaming layer and a PVC adhesive layer, and the steps are as follows:

[0029] Step 1: Prepare a PVC surface layer, weigh the PVC surface layer materials in sequence, stir them evenly, apply them by scraping, and put them into an oven for drying. The PVC surface layer materials include: 100 parts of PVC paste resin powder and 70-120 parts of plasticizer;

[0030] Step 2: Prepare a PVC foam layer, weigh the PVC foam materials in sequence and stir them evenly, apply a second coat of paint on the surface layer of step 1, and put them into an oven for drying. The PVC foam layer materials include: 100 parts of PVC paste resin powder, 80-120 parts of plasticizer, 2-5 parts of foaming agent, and 6-10 parts of the compound flame retardant as described above;

[0031] Step three: prepare a PVC bonding layer, weigh the PVC bonding layer materials in sequence and stir them evenly, apply a third coat of paint on the foaming layer of the above step two, and put it into an oven for drying. The PVC bonding layer materials include: 100 parts of PVC paste resin powder, 80-120 parts of plasticizer, and 6-10 parts of the compound flame retardant as described above.

[0032] After cooling to room temperature, ultra-soft flame-retardant PVC artificial leather is prepared.

[0033] Furthermore, the materials in step one also include 1-5 parts of color paste or color powder.

[0034] Furthermore, the materials in at least one of steps 1 to 3 also include 2-5 parts of calcium zinc stabilizer.

[0035] Furthermore, the temperature of the oven drying is 160-180 degrees.

[0036] Another aspect of the present invention is to provide the use of the above-mentioned compound flame retardant as a compound flame retardant for super soft PVC products.

[0037] Another aspect of the present invention is to provide an ultra-soft flame-retardant PVC artificial leather, which is prepared by the method as described above.

[0038] The present invention greatly reduces the amount of antimony trioxide used in the flame retardant application of ultra-soft PVC products with a high proportion of plasticizer, and the flame retardant effect is equal to or even exceeds the solution of using antimony trioxide alone.

[0039] The increased difficulty of flame retardant of super-soft PVC resin is related to the high content of plasticizers. Plasticizers will produce a large number of free radicals when burning. The key to flame retardant of super-soft PVC resin is to capture gas-phase free radicals and quench free radical chain reactions. Antimony trioxide is used in combination with halogen compounds to show excellent flame retardant efficiency. During the combustion process of PVC resin, hydrogen chloride gas is released in the initial decomposition. Antimony trioxide combines with hydrogen chloride to form chlorine oxide compounds. Chlorine oxide compounds further decompose to form SbCl3. SbCl3 decomposes under heat to produce Cl· free radicals. Cl· free radicals can combine with ·OH and H· free radicals in the flame to inhibit the free radical chain reaction, thereby preventing the combustion process. In addition, the vapor density of SbCl3 is greater than that of air, and it can cover the surface of the material, further isolating the air and inhibiting the further release of combustible gases.

[0040] In order to solve the problem of high difficulty in flame retardancy of ultra-soft PVC, the present invention selects a combination of phosphorus-nitrogen flame retardants with step-by-step temperature resistance and uses them in combination with antimony trioxide to enhance the flame retardancy in both the gas phase and the solid phase. The specific principle is as follows:

[0041] At the beginning of PVC ignition, low temperature-resistant nitrogen flame retardants, ammonium polyphosphate and inorganic hypophosphite flame retardants are the first to decompose, releasing P· capturing free radicals, while releasing non-combustible components such as nitrogen and ammonia to dilute the combustible gas components. As the flame temperature further increases, phosphate metal salts or polyphosphate melamine salts and carbon-forming agent components further decompose, further releasing non-combustible gases in the gas phase to play a diluting role, and forming metaphosphoric acid and polyphosphoric acid in the solid phase, promoting the decomposition of components in the PVC substrate into carbon. As the combustion process progresses, the fire source temperature further increases, and the high temperature-resistant organic hypophosphite gradually decomposes, releasing P· capturing free radicals, further quenching the gas phase free radical reaction. At the same time, the carbon layer synergist can play a role in stabilizing the acid source in the solid phase to promote the formation of the carbon layer. Therefore, although the antimony trioxide component is reduced and the gas phase flame retardant effect is reduced during the whole process, the combined phosphorus-nitrogen flame retardant with a step-by-step increase in temperature resistance achieves enhanced flame retardancy in the gas phase and solid phase, achieving better flame retardant effect and smoke suppression performance than antimony alone. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Combustion results of Examples 1-5;

[0043] Figure 2 Combustion results of Examples 6-10;

[0044] Figure 3 The combustion results of Comparative Examples 1-5 are shown. DETAILED DESCRIPTION

[0045] Example 1

[0046] 1. Add 30 parts of antimony trioxide, 8 parts of calcium diethylphosphinate, 15 parts of aluminum hypophosphite, 18 parts of ammonium polyphosphate, 16 parts of melamine, 8 parts of piperazine pyrophosphate, and 5 parts of zinc borate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0047] 2. The formula of PVC surface layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of calcium zinc stabilizer, 4 parts of color paste or color powder. Weigh them in sequence and stir them evenly. Apply them on high-temperature release paper and put them in an oven at 170 degrees for 2-5 minutes to dry.

[0048] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 90 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 3 parts of calcium zinc stearate stabilizer, and 10 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0049] 4. The PVC adhesive layer formula is the same as the foaming layer formula and operation except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare the ultra-soft flame-retardant PVC artificial leather.

[0050] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0051] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0052] The above samples were tested in 6 replicates, 4 with A-0 grade and 2 with B grade.

[0053] Example 2

[0054] 1. Add 35 parts of antimony trioxide, 9 parts of diethyl-monoethyl aluminum phosphinate, 15 parts of calcium hypophosphite, 15 parts of melamine phosphate, 14 parts of melamine cyanurate, 8 parts of CFA, and 4 parts of zinc hydroxystannate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0055] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0056] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 110 parts of plasticizer DPHP, 4 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 9 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0057] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0058] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0059] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0060] The above samples were tested in 6 replicates, 3 with A-0 grade and 3 with B grade.

[0061] Example 3

[0062] 1. Add 38 parts of antimony trioxide, 5 parts of aluminum hypophosphite, 15 parts of calcium diethylphosphinate, 17 parts of ammonium polyphosphate, 15 parts of melamine cyanurate, 7 parts of piperazine pyrophosphate, and 3 parts of zinc hydroxystannate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0063] 2. The PVC surface layer formulation and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0064] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 100 parts of plasticizer DPHP, 4 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0065] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0066] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0067] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0068] The above samples were tested in 6 replicates, 5 with A-0 grades and 1 with B grade.

[0069] Example 4

[0070] 1. Add 40 parts of antimony trioxide, 11 parts of calcium hypophosphite, 10 parts of aluminum diethylphosphinate, 16 parts of aluminum tripolyphosphate, 15 parts of melamine, 6 parts of piperazine pyrophosphate, and 2 parts of zinc stannate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0071] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0072] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 110 parts of plasticizer DPHP, 4 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0073] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0074] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0075] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0076] The above samples were tested in 6 replicates, 4 with A-0 grade and 2 with B grade.

[0077] Example 5

[0078] 1. Add 40 parts of antimony trioxide, 10 parts of lanthanum hypophosphite, 8 parts of calcium diethylphosphinate, 16 parts of polyphosphate melamine salt, 14 parts of melamine cyanurate, 8 parts of dicarboxyethylphenylphosphinate melamine salt, and 4 parts of zinc aluminate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0079] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0080] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 110 parts of plasticizer DPHP, 4 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0081] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0082] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0083] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0084] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0085] Example 6

[0086] 1. Add 43 parts of antimony trioxide, 10 parts of calcium hypophosphite, 10 parts of aluminum diethylphosphinate, 13 parts of melamine polyphosphate, 14 parts of melamine cyanurate, 6 parts of piperazine pyrophosphate, and 4 parts of zinc aluminate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0087] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0088] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 110 parts of plasticizer DPHP, 4 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0089] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0090] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0091] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0092] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0093] Example 7

[0094] 1. Add 45 parts of antimony trioxide, 7 parts of aluminum hypophosphite, 10 parts of diethyl-monoethyl aluminum phosphinate, 13 parts of melamine polyphosphate, 12 parts of melamine cyanurate, 9 parts of piperazine pyrophosphate, and 4 parts of calcium silicate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0095] 2. The PVC surface layer formulation and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0096] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 90 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0097] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0098] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0099] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0100] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0101] Example 8

[0102] 1. Add 45 parts of antimony trioxide, 14 parts of calcium hypophosphite, 5 parts of zinc diethylphosphinate, 15 parts of melamine phosphate, 11 parts of melamine, 6 parts of CFA, and 4 parts of magnesium hydroxide into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0103] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0104] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 100 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 3 parts of calcium zinc stearate stabilizer, and 8 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0105] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0106] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0107] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0108] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0109] Example 9

[0110] 1. Add 50 parts of antimony trioxide, 5 parts of calcium hypophosphite, 11 parts of aluminum diethylphosphinate, 12 parts of melamine phosphate, 12 parts of melamine, 6 parts of piperazine pyrophosphate, and 4 parts of aluminum hydroxide into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0111] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0112] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0113] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0114] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0115] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0116] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0117] Example 10

[0118] 1. Add 50 parts of antimony trioxide, 12 parts of aluminum hypophosphite, 6 parts of diethyl zinc hypophosphite, 13 parts of melamine phosphate salt, 10 parts of melamine cyanurate, 7 parts of piperazine pyrophosphate, and 2 parts of silicon dioxide into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0119] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0120] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of compounded flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0121] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0122] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0123] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0124] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0125] Comparative Example 1

[0126] 1. Prepare antimony trioxide powder;

[0127] 2. The PVC surface layer formulation and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0128] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, 9 parts of antimony trioxide flame retardant. Weigh them in sequence and stir evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees and dry them after 2-5 minutes.

[0129] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0130] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0131] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0132] The above samples were tested in 6 replicates, with 6 A-0 grades.

[0133] Comparative Example 2

[0134] 1. Add 50 parts of antimony trioxide, 20 parts of aluminum diethylphosphinate, and 30 parts of aluminum hypophosphite into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0135] 2. The PVC surface layer formulation and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0136] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of prepared flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0137] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0138] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0139] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0140] The above sample test was repeated for 6 groups, all of which were grade C, with a speed of 80-120mm / min and dripping;

[0141] Comparative Example 3

[0142] 1. Add 50 parts of antimony trioxide, 10 parts of aluminum diethylphosphinate, 15 parts of aluminum hypophosphite, and 25 parts of ammonium polyphosphate into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0143] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0144] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of prepared flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0145] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0146] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0147] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0148] The above sample test was repeated for 6 groups, all of which were grade C, with a speed of 30-60mm / min and dripping;

[0149] Comparative Example 4

[0150] 1. Add 50 parts of antimony trioxide, 8 parts of aluminum diethylphosphinate, 10 parts of calcium hypophosphite, 18 parts of polyphosphate melamine salt, and 14 parts of dimelamine into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0151] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0152] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of prepared flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0153] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0154] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0155] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0156] The above samples were tested in 6 groups, 2 were graded A-0, 4 were graded B, and there was dripping;

[0157] Comparative Example 5

[0158] 1. Add 50 parts of antimony trioxide, 9 parts of diethyl aluminum phosphite, 9 parts of aluminum hypophosphite, 18 parts of ammonium polyphosphate, 7 parts of dimelamine, and 7 parts of carbonizing agent CFA into a high-speed mixer and mix rapidly for 20 minutes to prepare a composite flame retardant powder;

[0159] 2. The PVC surface layer formula and treatment method are the same as those in Example 1, and the PVC surface layer is dried and set aside for use;

[0160] 3. The formula of PVC foaming layer is 100 parts of PVC paste resin powder, 80 parts of plasticizer DPHP, 3 parts of foaming agent azodicarbonamide, 4 parts of calcium zinc stearate stabilizer, and 10 parts of prepared flame retardant. Weigh them in sequence and stir them evenly. Apply the second coat on the surface resin layer applied in step 1 above, put them in an oven at 170 degrees, and dry them after 2-5 minutes.

[0161] 4. The formula of the PVC adhesive layer is the same as that of the foaming layer except that there is no foaming agent. After scraping, wet-paste the polyester cloth. After 2-5 minutes, it is cured and firmly attached. After cooling to room temperature, peel off the release paper to prepare an ultra-soft flame-retardant PVC artificial leather sample;

[0162] 5. Place the prepared leather products in an atmosphere with a temperature of 10-30°C and a relative humidity of 30-80% for 24 hours, and then cut them into standard flame retardant strips for testing.

[0163] According to the requirements of GB8410-2006 "Combustion Characteristics of Automobile Interior Materials", the flame retardancy of fabrics is evaluated by horizontal combustion. The object to be tested is exposed to the flame for 15 seconds. If it goes out within the first mark, it is A-0 mm / min, the best flame retardancy. If it goes out by itself within 60 seconds and the burning distance is ≤50 mm, it is B grade. Otherwise, it is C-burning speed, or D-burning speed, or E.

[0164] The above samples were tested in 6 replicates, 3 A-0 grades, 3 B grades, and slight dripping (1-2 drops).

[0165] In addition, all samples were tested for smoke density level according to GBT 8627-2007 "Test method for smoke density of burning or decomposition of building materials". Samples with specifications of (25.4±0.3) mm × (25.4±0.3) mm × (6.2±0.3) mm were prepared, placed in the frame slot, and ignited for testing. The smoke production was observed according to the relationship between light absorption and time shown on the display board. The equipment can directly obtain the smoke density level data.

[0166] The horizontal combustion results of the embodiments and comparative examples are shown in FIG. Figure 1-3 As shown, Figure 1 The combustion results of Examples 1-5 are: Figure 2 is the combustion result of Examples 6-10, Figure 3 The combustion results of comparative examples 1-5 are shown in the figure. The numbering order in the figure corresponds to the numbering order in the embodiment. In the figure, the marking line is a 38 mm marking line. It is judged whether it passes the optimal A-0 level. The length within 50 mm outside the marking line (and meets the extinguishing time requirement within 60 seconds from the start of timing) is B level, and it spreads to a longer distance for C or D level.

[0167] The horizontal combustion and smoke density level data of all embodiments and comparative examples are shown in Table 1.

[0168]

Claims

1. A compound flame retardant for ultra-soft PVC products, the compound flame retardant comprising an antimony trioxide component and a composite phosphorus-nitrogen flame retardant component, the composite phosphorus-nitrogen flame retardant component comprising: Organic phosphinate, inorganic phosphinate, phosphate, nitrogen-containing flame retardant, carbon-forming agent and optional carbon layer synergist. In the ultra-soft PVC product, based on 100 parts by weight of PVC resin, the content of plasticizer is 80-120 parts. The specific mass percentage composition of the compound flame retardant is: Antimony trioxide: 30%-50%; Organic phosphinate: 5%-15%; Inorganic hypophosphite: 5%-15%; Phosphate: 10%-20%; Nitrogen-containing flame retardant: 10%-20%; Carbon-forming agent: 5%-10%; Carbon layer enhancer: 0-5%; Wherein, the carbon-forming agent is selected from: one or more of piperazine pyrophosphate, piperazine diethylphosphinate, melamine dicarboxyethylphenylphosphinate, and triazine ring carbon-forming agent CFA; The carbon layer synergist is selected from one or more of magnesium hydroxide, aluminum hydroxide, zinc stannate, hydroxy zinc stannate, zinc aluminate, aluminum silicate, zinc silicate, silicon dioxide, and zinc borate.

2. The composite flame retardant according to claim 1, characterized in that: The PVC product is artificial leather.

3. The composite flame retardant according to claim 1, characterized in that: The mass ratio of the antimony trioxide and the composite phosphorus-nitrogen flame retardant component is 1:(1-2.33).

4. The composite flame retardant according to claim 1, characterized in that: The organic phosphinate or inorganic phosphite is selected from one or more of diethylaluminum phosphinate, diethylzinc phosphinate, diethylcalcium phosphinate, diethyl-monoethyl composite aluminum phosphinate, diisobutylaluminum phosphinate / dimethylaluminum phosphinate, aluminum phosphite, calcium phosphite, and lanthanum phosphite.

5. The composite flame retardant according to claim 1, characterized in that: The phosphate is selected from one or more of aluminum tripolyphosphate, zinc phosphate, magnesium phosphate, ammonium polyphosphate, melamine phosphate salt, and melamine polyphosphate salt.

6. The composite flame retardant according to claim 1, characterized in that: The nitrogen-containing flame retardant is selected from one or more of melamine, dimelamine, melamine cyanurate, and guanidine carbonate.

7. A method for preparing an ultra-soft flame-retardant PVC artificial leather, the PVC artificial leather comprising three layers: a PVC surface layer, a PVC foaming layer and a PVC adhesive layer, the steps of which are: Step 1: Prepare the PVC surface layer, weigh the PVC surface layer materials in sequence, stir them evenly, apply them by scraping, and put them into an oven for drying. The PVC surface layer materials include: 100 parts of PVC paste resin powder, 70-120 parts of plasticizer; Step 2: Prepare a PVC foam layer, weigh the PVC foam materials in sequence and stir them evenly, apply a second coat of paint on the surface layer of step 1, and put them into an oven for drying. The PVC foam layer materials include: 100 parts of PVC paste resin powder, 80-120 parts of plasticizer, 2-5 parts of foaming agent, and 6-10 parts of the compound flame retardant according to any one of claims 1 to 6; Step 3: Prepare a PVC bonding layer, weigh the PVC bonding layer materials in sequence and stir them evenly, apply a third coat of coating on the foaming layer in the above step 2, and put them into an oven for drying, wherein the PVC bonding layer materials include: 100 parts of PVC paste resin powder, 80-120 parts of plasticizer, and 6-10 parts of the compound flame retardant according to any one of claims 1-6; After cooling to room temperature, ultra-soft flame-retardant PVC artificial leather is prepared.

8. The method according to claim 7, characterized in that The materials in step 1 also include 1-5 parts of color paste or color powder.

9. The method according to claim 7, characterized in that The materials in at least one of steps 1 to 3 further include 2-5 parts of calcium zinc stabilizer.

10. Use of the compound flame retardant according to any one of claims 1 to 6 as a compound flame retardant for super soft PVC products.

11. An ultra-soft flame-retardant PVC artificial leather, prepared by the method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • An antimony oxide compounded flame retardant PVC soft composite material and its preparation method

    CN105086197B

  • A method for preparing composite flame-retardant flexible PVC resin

    CN108948596B

  • A flame-retardant and smoke-suppressing PVC composite material and its preparation method

    CN109467845B

  • Polyvinyl chloride composite flame retardant and preparation method thereof

    CN113214537A

  • Flame-retardant PVC (polyvinyl chloride) artificial leather and preparation process thereof

    CN103951913A